REPRESENTASI AKTOR DALAM PEMBERITAAN KORUPSI PT PERTAMINA DI MEDIA TEMPO.CO: ANALISIS WACANA KRITIS BERBASIS KORPUS - Wahyuni, Sri; Fadillah, Nurul (Universitas Hamzanwadi, 2025)
This study aims to reveal the ideology in Tempo.co media coverage through the representation of actors in the PT Pertamina corruption case. The method used is mixed method, by collecting 10 news texts from Tempo.co using the keywords “corruption” and “PT Pertamina”. A quantitative approach was applied to analyze the corpus data using the AntConc application. In contrast, a qualitative approach was used to identify the representation of actors in the news through Theo van Leeuwen's critical discourse analysis theory. The results of the analysis showed that Tempo.co framed the PT Pertamina corruption case by highlighting three main actors: PT Pertamina as the institutional actor, the Attorney General's Office as the law enforcer, and the state as the aggrieved party. This research also reveals that Tempo.co not only presents facts, but also forms a social construction that reflects anti-corruption ideology and favors transparency and public justice.